2016
DOI: 10.3748/wjg.v22.i11.3196
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of re-bleeding after endoscopic hemostasis for delayed post-endoscopic sphincterotomy bleeding

Abstract: Re-bleeding occurs in approximately one-fifth of patients after initial successful endoscopic hemostasis for delayed post-ES bleeding. Severity of initial bleeding and serum bilirubin level of greater than 10 mg/dL are predictors of re-bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
0
14
0
4
Order By: Relevance
“…[23] Endoscopic hemostasis is currently the first choice of treatment for post-ERCP bleeding, whereas angiography or surgery can serve as alternative rescue management if endoscopic hemostasis fails to stop the hemorrhage. [24] Therefore, we chose the recording of a of post-ERCP endoscopic hemostasis procedure in the NHIRD as a surrogate marker for post-EST or post-EPBD major bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Endoscopic hemostasis is currently the first choice of treatment for post-ERCP bleeding, whereas angiography or surgery can serve as alternative rescue management if endoscopic hemostasis fails to stop the hemorrhage. [24] Therefore, we chose the recording of a of post-ERCP endoscopic hemostasis procedure in the NHIRD as a surrogate marker for post-EST or post-EPBD major bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, immediate bleeding in three of 13 patients was aborted using only epinephrine spray only and 10 patients required further endoscopic hemostasis by epinephrine injection. Past studies have shown that rebleeding after initially successful endoscopic hemostasis for EST bleeding is as high as 21.7%, and the severity of the initial bleeding and a high serum bilirubin of more than 10 mg/dL are predictors of rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…There is a reduction of vitamin K absorption due to cholestasis condition and the patients might have the hemorrhagic diathesis [9,10]. To our knowledge, there are only two previous studies showing that high bilirubin level is an independent risk factor in obstructive jaundice patients who underwent intervention procedures; however in one study the sample size was too small and in another study patients with decompensated liver cirrhosis and the use of anti-platelet before sphincterotomy were included [11,12]. In our study the population is more homogenous and it might be the reason of different finding.…”
Section: Discussionmentioning
confidence: 99%